Melon Aphid or Cotton Aphid, Aphis gossypii Glover (Insecta: Hemiptera: Aphididae) - John L. Capinera (EDIS)
Melon aphid occurs in tropical and temperate regions throughout the world except northernmost areas. In the United States, it is regularly a pest in the southeast and southwest, but is occasionally damaging everywhere. Because melon aphid sometimes overwinters in greenhouses, and may be introduced into the field with transplants in the spring, it has potential to be damaging almost anywhere. This document is EENY-173, one of the Featured Creatures series of the Entomology and Nematology Department, Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: November 2000.